Modern Capabilities of Laser Surgery for Closed-Angle Glaucoma (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The literature review discusses modern laser surgical approaches in primary angle-closure glaucoma. Epidemiology, pathogenesis, efficacy of laser peripheral iridotomy, iridoplasty, selective laser trabeculoplasty, and early lens extraction are analyzed. LPI is effective for pupillary block, while complex anatomical cases benefit from combined approaches. Phacoemulsification provides more stable IOP control and reduces long-term complications.